Croatian Constitutionalism from Autonomy to the State - Čepulo, Dalibor (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
Croatian regions in Austro-Hungary, among which the autonomous kingdoms of Croatia and Slavonia, had a special significance, entered the newly created unitary Yugoslav kingdom in 1918. The initial enthusiasm for the unification was replaced by the dissatisfaction of Croats, whose interests were then satisfied within the autonomous Banate of Croatia formed in 1939. After the break-up of the Yugoslav kingdom, the short-lasting puppet state Independent State of Croatia was established in 1941, while the foundations of the Yugoslav communist federation with federal Croatia were laid down in 1943 and transformed into constitutional form in 1946 and 1947. For a long time, the federal centre dominated the formally sovereign republics, but the wide decentralisation in 1974 enabled Croatia to establish constitutional and legislative framework that later became the basis of its transition to independence. Only a few elements from that period are retained in the Constitution of the Republic of Croatia of 1990, which was set on a completely new basis modelled on Western constitutionality. The core line of Croatian constitutional development is grounded upon its autonomy in the decentralised and multi-cultural frameworks and building-up of independence.KEYWORDS: Croatian constitutional development, Croatian constitution, Croatian autonomy, self-determination of peoples, right to secession, dissolution of Yugoslavia.